Profiling the training practices and performance of elite rowers - Tran, J.; Rice, A. J.; Main, L. C.; Gastin, P. B. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate changes in physiology, performance, and training practices of elite Australian rowers over 6 mo. Methods: Twenty-one elite rowers (14 male, 7 female) were monitored throughout 2 phases: phase 1 (specific preparation) and phase 2 (domestic competition). Incremental tests and rowing-ergometer time trials over 100, 500, 2000, and 6000 m were conducted at the start of the season, midseason, and late season. Weekly external (frequency, duration, distance rowed) and internal (T2minute method) loads are reported. Results: Heavyweight male rowers achieved moderate improvements in VO2max and power at VO2max. Most other changes in physiology and performance were small or unclear. External loads decreased from phase 1 to phase 2 (duration 19.3 to 18.0 h/wk, distance rowed 140 to 125 km/wk, respectively). Conversely, internal loads increased (phase 1 = 19.0 T2hours, phase 2 = 20.3 T2hours). Low-intensity training predominated (~80% of training hours at T1 and T2), and high-intensity training was greater in phase 2. Training was rowing-focused (68% of training duration), although 32% of training time was spent in nonspecific modes. The distribution of specificity was not different between phases. Conclusion: Physiology and performance results were stable over the 6-mo period. Training-load patterns differed depending on the measure, highlighting the importance of monitoring both external and internal loads. The distribution of intensity was somewhat polarized, and substantial volumes of nonspecific training were undertaken. Experimental studies should investigate the effects of different distributions of intensity and specificity on rowing performance.